“El estudio de los elementos de Motivación del Personal y la Productividad de la empresa bananera “Buenos Aires” del cantón Valencia”. - Candelo Moya, Anddy Melanie (2022)
The general objective of this research is to analyze the study of the elements of personnel motivation and productivity of the banana company "Buenos Aires" in the canton of Valencia, it can be said that personnel motivation within companies is something that goes beyond the various incentive programs for staff who are working in these entities while productivity is an economic measure that in one way or another helps to calculate how many goods and services have been produced for each factor used (worker, capital, time, land) during a given period, Banana is the most important product of the country, it is an export product and also contributes directly to the economy of our country, being one of the most exported fresh fruits in the world in terms of volume and value. To this end, the different elements of each one of the variables that are immersed in this research project are studied, with emphasis on personnel motivation and productivity according to the position, job, etc. For this purpose, descriptive research will be used, describing all the topics and processes related to labor motivation and productivity; field research will proceed to collect the information in the study site in this case the banana company, where the techniques of interviews to the manager and surveys to the personnel of the banana company will be applied, which will allow knowing the degree of motivation of the human talent that works in the company, for them it was necessary to use the bibliographic type of research, field research. Among the methods to be used is the inductive-deductive method by means of which conclusions will be drawn about the study, and the analytical-synthetic method that allows the analysis of all the information collected. For the validation of the instruments, expert judgment is used and reliability is obtained by means of a test, from which different conclusions will be drawn according to the results. With regard to the proposal proposed in the research on training and labor incentives, it could be evidenced that through the implementation of the proposal it will be possible to directly improve the productivity of the company.